SOCIAL DETERMINANTS CHARACTERISTICS OF TUBERCULOSIS PATIENTS IN BANDAR LAMPUNG MUNICIPALITY - Diah Wulan Sumekar Rengganis Wardani (Fakultas Kedokteran Universitas Lampung, 2014)
Background: World Health Organization through tuberculosis (TB) control averted up to six million deaths and cured thirty-six million people in 1995-2008, but had less success in reducing TB incidence, especially in thirteen high burden countries, including Indonesia. Therefore, TB control will need to have more emphasis on the issues of social determinants, as social determinants affect TB’s incidence directly and/-or through TB’s risk factors. This study aimed to identify social determinants characteristics of TB patients in Bandar Lampung, during period January–July 2012. Methods: The research setting was at twenty-seven primary health centers and one hospital that have implemented the Directly Observed Treatment Shortcourse (DOTS) strategy in Bandar Lampung. Respondents of this research were 238 TB patients and 238 patients without TB. Research variables consisted of social determinants, which measured through its indicators (education, occupation, family income, and social class). Data have been collected by using questionnaire and then was analyzed with Stata 11. Results: Tuberculosis patients had lower education, occupation, family income, and social class compare to patients without TB. Conclusion: The knowledge of social determinants characteristics of TB patients can be used to support TB control program, particularly to implement DOTS strategy together with improving social determinants. [JuKe Unila 2014; 4(8):166-172]